Cyclic Hypervalent Iodine Reagents for Atom-Transfer Reactions: Beyond Trifluoromethylation - Li, Yifan; Hari, Durga Prasad; Vita, Maria Victoria; Waser, Jerome (Angewandte Chemie International Edition, 2016)
Hypervalent iodine compounds are privileged reagents in organic synthesis because of their exceptional reactivity. Among these compounds, cyclic derivatives stand apart because of their enhanced stability. They have been widely used as oxidants, but their potential for functional‐group transfer has only begun to be investigated recently. The use of benziodoxol(on)es for trifluoromethylation (Togni's reagents) is already widely recognized, but other transformations have also attracted strong interest recently. In this Review, the development in the area since 2011 will be presented. After a short summary of synthetic methods to prepare benziodoxol(on)e reagents, their use to construct carbon–heteroatom and carbon–carbon bonds will be presented. In particular, the introduction of alkynes by using ethynylbenziodoxol(on)e (EBX) reagents has been highly successful. Breakthroughs in the introduction of alkoxy, azido, difluoromethyl, and cyano groups will also be described. The exceptional reactivity of hypervalent iodine compounds make them privileged reagents in organic synthesis. Of them, cyclic derivatives stand apart because of their enhanced stability. The use of benziodoxol(on)es for trifluoromethylation (Togni's reagents) is now well recognized, but other transformations have also attracted strong interest recently. The progress in the area since 2011 is presented in this Review. Q=8‐aminoquinoline.